2022
DOI: 10.3390/lubricants10090211
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Eco-Friendly Non-Edible Vegetable Oils in Drilling Inconel 718 through Minimum Quantity Lubrication

Abstract: Metal cutting fluids (MCFs) have played a principal role as coolants and lubricants in the machining industry. However, the wide use of mineral-based oil MCFs has contributed to an adverse effect on humans and the environment. Thus, to overcome the adverse effects of mineral-based oil MCFs, eco-friendly vegetable oil, which is non-edible oil, has been implemented to overcome the issues related to edible oil such as manufacturing costs and food shortages. This study investigated the performance of three differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…For environmental protection and resource efficiency, minimum quantity lubrication (MQL) and biolubricants offer a high potential [8][9][10]. In the case of biolubricants under MQL conditions, Safie et al investigated rice bran oil, neem oil, and castor oil and showed some benefits with castor oil [11]. Compared with mineral cutting fluid, vegetable-oil-based emulsion can feature better properties for the turning of AISI 1050 steel by improving machinability as shown by Carvalho et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…For environmental protection and resource efficiency, minimum quantity lubrication (MQL) and biolubricants offer a high potential [8][9][10]. In the case of biolubricants under MQL conditions, Safie et al investigated rice bran oil, neem oil, and castor oil and showed some benefits with castor oil [11]. Compared with mineral cutting fluid, vegetable-oil-based emulsion can feature better properties for the turning of AISI 1050 steel by improving machinability as shown by Carvalho et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Conventional CFs, on the other hand, are ineffective in high-speed machining. 8,9 Other significant issues generated by conventional CFs include health and environmental concerns. 10,11 The other problems encountered during the use of metal working fluids are clearly shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%